2021
DOI: 10.1101/2021.02.02.21250960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Colchicine use in patients with COVID-19: a systematic review and meta-analysis

Abstract: Introduction: Colchicine may inhibit inflammasome signaling and reduce proinflammatory cytokines, a purported mechanism of COVID-19 pneumonia. The aim of this systematic review and meta-analysis is to report on the state of the current literature on the use of colchicine in COVID-19 and to investigate the reported clinical outcomes in COVID-19 patients by colchicine usage. Methods: The literature was searched from January 2019 through January 28, 2021. References were screened to identify studies that reported… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
9
1
5
Order By: Relevance
“…Colchicine is not beneficial in reducing risk of mortality in patients with COVID-19. However, earlier meta-analysis studies done by Chiu et al 13 , Vrachatis et al 16 and Hariyanto et al 14 concluded that colchicine may reduce the mortality risk among patients with COVID-19. A living systematic review and network meta-analysis conducted by Siemieniuk et al 25 concluded that colchicine may reduce mortality and mechanical ventilation in non-severe patients with COVID-19.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Colchicine is not beneficial in reducing risk of mortality in patients with COVID-19. However, earlier meta-analysis studies done by Chiu et al 13 , Vrachatis et al 16 and Hariyanto et al 14 concluded that colchicine may reduce the mortality risk among patients with COVID-19. A living systematic review and network meta-analysis conducted by Siemieniuk et al 25 concluded that colchicine may reduce mortality and mechanical ventilation in non-severe patients with COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“…Few systematic reviews conducted earlier on the safety and efficacy of colchicine in COVID-19 management included observational studies in their analysis pool. 13–16 Now, randomised controlled trials (RCTs) are available evaluating the use of colchicine in patients with COVID-19. Hence, this meta-analysis was conducted with an objective to determine the efficacy and safety outcomes in patients with COVID-19 treated with colchicine.…”
Section: Introductionmentioning
confidence: 99%
“…Установлено, o n l i n e fi r s t что у пациентов с COVID-19 лечение колхицином приводит к снижению риска госпитализаций (на 25%), потребности в ИВЛ (на 50%) и летальности (на 44%). Данные об эффективности колхицина при COVID-19 подтверждена в метаанализах открытых исследований и РКИ [148]. Другим препаратом, широко применяющимся для лечения ИВРЗ, является тБПВП барицитиниб (БАРИ), механизм действия которого связан с ингибицией Янус-киназ, опосредующей антивирусный и противовоспалительный эффекты этого препарата [149].…”
Section: Discussionunclassified
“…Similar results were reported by Hariyanto et al [ 104 ]. Chiu et al included six studies (3 observational studies and 3 randomized trials) having included 5033 patients and reported mortality risk reduction with colchicine administration (OR 0.36; 95% CI: 0.17–0.76), but this survival benefit was no longer significant when analyzing only randomized trial data (OR 0.49; 95% CI: 0.20–1.24) [ 105 ]. More recent meta-analyses of COVID-19 studies have also reported benefits of colchicine administration on mortality [ 106 , 107 , 108 , 109 ].…”
Section: Colchicine and Covid-19 Infectionmentioning
confidence: 99%